Production performance of closed water fishery resources in Narayangonj-Narsingdi Irrigation Project - Hossain, Md Motaher; Shafi, Mohammed; Ahmed, Md Kawser (Dhaka University Journal of Biological Sciences, 2012)
A survey was conducted both inside (flood?free zone and flooded zone) and outside the embankment of Narayangonj?Narsingdi Irrigation Project, Rupgonj, Narayanganj. All ponds and borrow pits were surveyed from the randomly 10% selected villages by using pre?tested questionnaires. The highest production was in semi?intensive ponds (3,827 and 3,979 kg/ha) in flood?free zone, (3,911 and 4,000 kg/ha) in flooded zone and (3,800 and 4,000 kg/ha) in outside zone, while, the lowest production was found (1,756 and 1,759 kg/ha) in flood?free zone, (1,603 and 1,646 kg/ha) in flooded zone and (1,699 and 1,706 kg/ha) in outside zone in 2003?2004 and 2004?2005, respectively. It was also observed that the production of culturable ponds was higher (959 and 942 kg/ha) in outside, followed by flooded zone (950 and 917 kg/ha) and the lowest production in flood?free zone (400 and 356 kg/ha) in 2003?2004 and 2004?2005. The highest average production of fishes in closed water (ponds and borrow pits) was found in flood?free zone (23,277 and 2,368 kg/ha), followed by flooded zone (2,249 and 2,336 kg/ha) and the lowest average production in outside zone (1,972 and 1,985 kg/ha) in 2003?2004 and 2004?2005, respectively. The higher significant difference (p<0.001) was found between the production of flood?free zone and outside zone in both 2003?2004 and 2004?2005, where no significant difference (p > 0.05) was found between the production of flooded zone and outside zone both in both years. DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11512 Dhaka Univ. J. Biol. Sci. 21(2): 141-152, 2012 (July)